Impact of the Physician Orders for Life-Sustaining Treatment (POLST) Program Maturity Status on the Nursing Home Resident’s Place of Death - Tark, Aluem (Am J Hosp Palliat Care, 2020)
The Physician Orders for Life-Sustaining Treatment (POLST) program was developed to enhance quality of care delivered at end-of-life. Although positive impacts of the POLST program have been identified, the association between a program maturity status and nursing home resident’s likelihood of dying in their current care settings remain unanswered. This study aims to evaluate the impact of the POLST program maturity status on nursing home residents’ place of death. Using multiple national level datasets, we examined 595,152 residents and their place of death. The result showed that the long-stay residents living in states where the program was mature status had 12% increased odds of dying in nursing homes compared that of non-conforming status. Individuals residing in states with developing program status showed 11% increase in odds of dying in nursing homes. The findings demonstrate that a well-structured advance care planning program may enhance care outcomes among nursing home residents.